If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6) + 9 = -9 Reorder the terms: 3(-6 + x) + 9 = -9 (-6 * 3 + x * 3) + 9 = -9 (-18 + 3x) + 9 = -9 Reorder the terms: -18 + 9 + 3x = -9 Combine like terms: -18 + 9 = -9 -9 + 3x = -9 Add '9' to each side of the equation. -9 + 9 + 3x = -9 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = -9 + 9 3x = -9 + 9 Combine like terms: -9 + 9 = 0 3x = 0 Solving 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 0 Simplifying x = 0
| 29=5x-2(10-x) | | (2/3)(k-8)=52 | | 9.7y+2.16=11.42 | | y-11=(5/11)(x-10) | | 0.25(16-4x)=7-(1.25x+5) | | x-5y=17fory | | 4g+17=81 | | Xsquared+8x+15=0 | | 73774t+132=11 | | 4(2-3x)-(6x-4)=2(5-5x) | | h=32+48t-16t^2 | | 8n+19=4n+135 | | 2(3.14r)=20 | | 2x+8=25-9x | | 3*(X+2)=15 | | -6.1y=198.25 | | 12c-5c= | | w-16=28 | | 2/3x13 | | 5x^2+21x-4=0 | | -[-[-(6x+5)]]=-(x+5) | | 2(3p-t)-(-4p+t)= | | 24+p=54 | | 0.7r=-91 | | 6-6x=3y | | 11c+1=67 | | A(9+a)=4(2a+5) | | 54v^2+18v-120=0 | | r=f(w+a) | | Y(2)-3y+2=0 | | 13/10 | | 4.37=19p |